Measuring connectivity and navigational paths in an elearning environment (Virtual Campus) - Blank, Daniel (2002)
This paper introduces the Campus Virtual Notredame (CVN) e-learning environment, a multi-campus schema supporting the development of programs for different institutions. CVN handles both academic and administrative tasks. It also provides statistics of usage, over standard periods of time, with the help of a graphical representation tool. The objective is to model the behavior of the agents in the virtual e-learning environment and use the statistics and tool to help to optimize the contents of the campus. The data collected would also allow to plot the path the users follow in the campus pages (called navigation graph). Although further research is needed we believe that the metrics can be correlated with the academic performance of students.